2021
DOI: 10.1108/md-10-2020-1356
|View full text |Cite
|
Sign up to set email alerts
|

Can abusive supervision create positive work engagement? The interactive moderating role of positive causal attribution and workplace friendship

Abstract: PurposeDeparting from previous research which shows that abusive supervision, as a salient job demand, induces detrimental employee outcomes, this study examines how to create constructive consequences of abusive supervision. To do so, the authors identify the boundary conditions to change the negative effect of supervisory abuse on employees’ work engagement in a positive direction. The authors examine the interactive moderating effect of a personal resource (i.e. positive causal attribution of abusive superv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 74 publications
1
6
0
Order By: Relevance
“…In addition, employees in teams with an abusive supervision climate can benefit from workplace programs that promote building coworker support (Rasheed et al , 2021) and friendship (Huh and Lee, 2022). They would also benefit from training in coping strategies (Srikanth, 2020), building psychological flexibility (Asim et al , 2023) and attribution training to focus on more positive attributions (Huh and Lee, 2022; Martinko et al , 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, employees in teams with an abusive supervision climate can benefit from workplace programs that promote building coworker support (Rasheed et al , 2021) and friendship (Huh and Lee, 2022). They would also benefit from training in coping strategies (Srikanth, 2020), building psychological flexibility (Asim et al , 2023) and attribution training to focus on more positive attributions (Huh and Lee, 2022; Martinko et al , 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Spreitzer (1995) conducted a survey with Fortune 50 mid-level and found similar results, where high levels of performance feedback were related to high levels of motivation. Recent research has shown that supervisor interaction (Huh and Lee, 2022) and empowerment (Arshad et al ., 2021), including performance feedback, positively impact workers' engagement.…”
Section: Background and Hypothesesmentioning
confidence: 99%
“…Abusive practices do not manifest as isolated in the schools, but as an extension of behaviour emanating from communities or home environment. You would find that these leaders who practice it either do the same to their siblings, children or partners (Huh & Lee, 2021). Mackey, Frieder, Brees and Martinko (2017) identify two distinguishable subjective perceptions, one of which speaks to what supervisory leaders do (e.g., derogatory comments, uncontrolled outbursts, strategic undermining behaviour) and one of which addresses employees' attitudes toward their supervisors.…”
Section: Conceptualizing Characterizing and Identifying Abusive Schoo...mentioning
confidence: 99%